Word Formation Processes in There Will Come Soft Rains Short Story - Elizabeth Emmanuela Sulistyawati; Barli Bram (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2021)
Many English words were formed through word-formation processes that can be found in English literary works, such as novels and short stories. One of the examples is the short story There Will Come to Soft Rains written by Ray Bradbury. Therefore, the researchers aimed to investigate the word-formation processes in the short story in order to answer a research question, namely: What word-formation processes occur in the story of There Will Come Soft Rains by Ray Bradbury? This research was conducted by using document analysis since it used a short story as the source of data. The results showed that 4 lexical items formed through cliticization, 22 lexical items through compounding, and 44 lexical items through derivation. With 44 instances, derivation, forming words by adding affixes, particularly prefixes and suffixes, was the most frequent word-formation process used in the short story.